High-nickel ternary material with selenium-doped surface as well as preparation method and application of high-nickel ternary material

By performing gas-phase selenization on high-nickel ternary materials, a high-nickel ternary material with surface selenium doping is formed, which solves the problem of insufficient cyclic stability and rate performance of the material in lithium-ion batteries, and achieves higher electrochemical cyclic stability and thermal stability.

CN119833577APending Publication Date: 2025-04-15CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311317249.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

There is a lack of cycle stability, rate performance and thermal stability of high-nickel ternary materials in lithium-ion batteries, mainly due to the instability at the cathode-electrolyte interface.

Method used

High-nickel ternary material is obtained by high-temperature solid phase reaction, and a high-nickel ternary material with surface selenium doped by gas phase selenization is formed by a heat treatment method. Selenium replaces part of oxygen to form metal selenide, which exists on the surface of the material, enhancing the stability of the material and its interaction with the electrolyte.

Benefits of technology

It improves the electrochemical cycle stability and rate performance of the material, slows down the side reactions at the material-electrolyte interface, and enhances the thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833577A_ABST
    Figure CN119833577A_ABST
Patent Text Reader

Abstract

The invention relates to a surface-selenium-doped high-nickel ternary material and a preparation method and application thereof. The surface-selenium-doped high-nickel ternary material comprises particles with the chemical formula of LiNixCoyMnzO2-pSep, x + y + z = 1, x is larger than or equal to 0.6 and smaller than or equal to 0.9, y is larger than or equal to 0.05 and smaller than or equal to 0.2, z is larger than 0.05 and smaller than or equal to 0.2, and p is larger than 0 and smaller than or equal to 0.2. In an XPS spectrogram of the Se < 3d > orbit of the high-nickel ternary material, a peak exists at 53-56 eV. When the high-nickel ternary material disclosed by the invention is used as a lithium ion positive electrode material, side reaction at a material-electrolyte interface can be slowed down, and the electrochemical cycle performance of the material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of preparation of ternary materials for lithium-ion batteries, and in particular to a surface selenium-doped high-nickel ternary material and a preparation method and application thereof. Background Art

[0002] As a high-capacity cathode material, high-nickel ternary materials have received extensive attention and are expected to meet the high energy density requirements of lithium-ion batteries. However, due to the structural defects of the material itself (cation mixing, oxygen vacancies, lithium vacancies, phase transitions and surface reconstruction, etc.), the poor electrochemical stability of the electrolyte, the high activity of tetravalent nickel ions, the safety issues caused by the decomposition and gas generation of the electrolyte, the side reactions at the interface, the dissolution of transition metals, the volume changes and microcracks caused by anisotropy during the cycle, and the generation of residual alkali on the surface, the high-nickel ternary materials still have certain deficiencies in cycle stability, rate performance and thermal stability, which limits their further practical application. Studies have shown that the roots of the above problems all start from or indirectly act on the cathode-electrolyte interface, ultimately leading to poor electrochemical performance of the battery. Therefore, improving the stability at the cathode-electrolyte interface is expected to optimize the electrochemical performance of high-nickel ternary materials.

[0003] Surface coating is an effective method to improve the stability of the electrode-electrolyte interface. It can not only prevent the formation of residual alkali on the surface, but also inhibit the occurrence of surface side reactions. However, existing surface coating technologies often involve mechanical mixing of precursors, making it difficult to achieve uniform coating of the material surface. In addition, there is often a certain surface energy between the coating material and the main material, which can easily lead to structural deformation. Summary of the invention

[0004] The purpose of the present invention is to provide a surface selenium-doped high-nickel ternary material and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned object, the present disclosure provides a surface selenium-doped high-nickel ternary material in a first aspect, wherein the surface selenium-doped high-nickel ternary material comprises a chemical formula of LiNi x Co y Mn z O 2-p Se p Particles, x+y+z=1, 0.6≤x≤0.9, 0.05≤y≤0.2, 0.05≤z≤0.2, 0<p≤0.2;

[0006] In the XPS spectrum of the Se 3d orbital of the high-nickel ternary material, there is a peak at 53-56 eV.

[0007] Optionally, in the particles, at least part of the selenium element exists in the form of metal selenide;

[0008] The metal selenide includes Ni selenide, Co selenide and Mn selenide;

[0009] Optionally, the metal selenide is present on the surface of the particles.

[0010] Optionally, the average particle size of the particles is 3-18 μm.

[0011] A second aspect of the present disclosure provides a method for preparing a surface selenium-doped high-nickel ternary material, the method comprising the following steps:

[0012] S1, mixing a lithium source and a high-nickel ternary precursor in a solid phase, and subjecting the obtained mixed material to a first heat treatment in an oxygen-containing atmosphere to obtain a first solid material;

[0013] S2. Contacting the selenium source with the first solid material, and performing a second heat treatment under an inert atmosphere.

[0014] Optionally, the chemical formula of the high nickel ternary precursor is Ni a Co b Mn c (OH)2, a+b+c=1, 0.6≤a≤0.9, 0.05≤b≤0.2, 0.05≤c≤0.2;

[0015] The average particle size of the high-nickel ternary precursor is 3-18 μm.

[0016] Optionally, the selenium source includes one or more of selenium, sodium selenite and ammonium selenite;

[0017] The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

[0018] Optionally, in step S2, the molar ratio of the selenium source to the first solid material, calculated as selenium element, is (0.05-5):10.

[0019] Optionally, in step S1, the first heat treatment is performed by calcination, and the conditions of the first heat treatment include: a time of 10-20 hours, a temperature of 600-850° C., and the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere;

[0020] In step S2, the second heat treatment is performed by calcination, and the conditions of the second heat treatment include: a time of 1-5 hours, a temperature of 400-700° C., and the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0021] Optionally, in step S1, the solid phase mixing method includes solid phase ball milling for 1-5 hours.

[0022] Optionally, step S2 is performed in a tube furnace, comprising: placing the selenium source upstream of the tube furnace, and placing the first solid material downstream of the tube furnace;

[0023] The selenium source generates a fluid containing selenium under high temperature, and the fluid containing selenium flows to the downstream of the tube furnace and contacts the first solid material.

[0024] The third aspect of the present disclosure provides a surface selenium-doped high-nickel ternary material prepared by the method described in the second aspect of the present disclosure.

[0025] A fourth aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the surface selenium-doped high-nickel ternary material as described in the first aspect or the third aspect of the present disclosure.

[0026] Through the above technical scheme, the present application first obtains a high-nickel ternary material through a high-temperature solid-phase reaction, and then obtains a surface selenium-doped high-nickel ternary material through a method of vapor phase selenization followed by heat treatment. In the surface selenium-doped high-nickel ternary material disclosed in the present invention, the selenium element replaces at least part of the oxygen element, and at least part of the selenium element exists in the form of a metal selenide and exists on the surface of the material, while ensuring the structure, the advantage of its strong interaction with the ternary material is brought into play, which can not only stabilize the metal elements on the surface of the material to improve the stability of the material itself, but also slow down the side reactions at the material-electrolyte interface, and use it as a positive electrode material for lithium-ion batteries, which can effectively improve the stability of the electrochemical cycle.

[0027] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0029] Figure 1 Electrochemical cycle curves of high nickel ternary materials A1 and D1 prepared in Example 1 and Comparative Example 1 of the present disclosure.

[0030] Figure 2 This is the X-ray photoelectron spectrum of Se 3d orbitals in the high-nickel ternary material A3 prepared in Example 3 of the present disclosure.

[0031] Figure 3 X-ray photoelectron spectra of Co 2p orbitals in high-nickel ternary materials A3 and D3 prepared in Example 3 and Comparative Example 3 of the present disclosure.

[0032] Figure 4 X-ray photoelectron spectra of Mn 2p orbitals in high-nickel ternary materials A3 and D3 prepared in Example 3 and Comparative Example 3 of the present disclosure.

[0033] Figure 5 This is a scanning electron microscope image of the high-nickel ternary material A4 prepared in Example 4 of the present disclosure.

[0034] Figure 6 This is a scanning electron microscope image of the high-nickel ternary material D4 prepared in Comparative Example 4 of the present disclosure. DETAILED DESCRIPTION

[0035] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0036] The present disclosure provides a surface selenium-doped high-nickel ternary material in a first aspect. The surface selenium-doped high-nickel ternary material comprises a chemical formula of LiNi x Co y Mn z O 2-p Se p Particles, x+y+z=1, 0.6≤x≤0.9, 0.05≤y≤0.2, 0.05≤z≤0.2, 0<p≤0.2;

[0037] In the XPS spectrum of the Se 3d orbital of the high-nickel ternary material, there is a peak at 53-56 eV.

[0038] According to one embodiment of the present disclosure, in the particles, at least part of the selenium element exists in the form of metal selenides; the metal selenides include Ni selenides, Co selenides and Mn selenides; wherein the existence form of the selenium element is tested by X-ray photoelectron spectroscopy.

[0039] In the present disclosure, "in the particles, at least part of the selenium element exists in the form of metal selenide" means that part or all of the selenium element in the particles exists in the form of metal selenide, and preferably all of the selenium element exists in the form of metal selenide; the present disclosure does not specifically limit the ratio of Ni selenide, Co selenide and Mn selenide. Ni selenide can be, for example, nickel selenide, Co selenide can be, for example, cobalt selenide, and Mn selenide can be, for example, manganese selenide; in the high-nickel ternary material of the present disclosure, the selenium element replaces at least part of the oxygen element to form a selenide with the metal, and the valence of the selenium element in the metal selenide is -2. While ensuring the material structure, it takes advantage of its strong interaction with the ternary material, which can not only stabilize the metal elements on the surface of the material to improve the stability of the material itself, but also slow down the side reactions at the material-electrolyte interface, and finally achieve an effective improvement in the electrochemical cycle stability of the material.

[0040] According to one embodiment of the present disclosure, the metal selenide exists on the surface of the particle. Specifically, the metal selenide partially or completely covers the surface of the particle. Preferably, the metal selenide completely covers the surface of the particle.

[0041] According to one embodiment of the present disclosure, the particles have a spherical and / or quasi-spherical morphology, and the definitions of spherical and quasi-spherical are conventional in the art; the average particle size of the particles is 3-18 μm.

[0042] A second aspect of the present disclosure provides a method for preparing a surface selenium-doped high-nickel ternary material, the method comprising the following steps:

[0043] S1, mixing a lithium source and a high-nickel ternary precursor in a solid phase, and subjecting the obtained mixed material to a first heat treatment in an oxygen-containing atmosphere to obtain a first solid material;

[0044] S2. Contacting the selenium source with the first solid material, and performing a second heat treatment under an inert atmosphere.

[0045] According to one embodiment of the present disclosure, the chemical formula of the high nickel ternary precursor is Ni a Co b Mn c (OH)2, a+b+c=1, 0.6≤a≤0.9, 0.05≤b≤0.2, 0.05≤c≤0.2; preferably, 0.7≤a≤0.9, 0.1≤b≤0.15, 0.1≤c≤0.15.

[0046] According to one embodiment of the present disclosure, the average particle size of the high-nickel ternary precursor is 3-18 μm, preferably 5-15 μm.

[0047] In the present disclosure, in order to achieve uniform mixing, in step S1, the solid phase mixing method may be solid phase ball milling for 1-5 hours; the solid phase ball milling may be performed on a planetary ball mill, for example.

[0048] According to one embodiment of the present disclosure, the selenium source and the lithium source are conventional in the art. For example, the selenium source includes one or more of selenium element, sodium selenite and ammonium selenite. When the selenium source includes more than two substances, the present disclosure does not impose specific restrictions on their proportions. The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate. When the lithium source includes more than two substances, the present disclosure does not impose specific restrictions on their proportions.

[0049] According to one embodiment of the present disclosure, the molar ratio of the selenium source calculated as selenium element to the first solid material is (0.05-5):10, preferably (0.05-2):10, and further preferably (0.1-2):10; the selenium source is partially lost during the heat treatment process, and the above ratio is met. On the basis of obtaining a high-nickel ternary material with better performance, effective surface modification of the selenium element can be achieved.

[0050] According to one embodiment of the present disclosure, the molar ratio of the lithium source calculated as lithium element to the high-nickel ternary precursor may be (0.8-1.2):1, and part of the lithium source is lost during ball milling and heat treatment.

[0051] According to an embodiment of the present disclosure, in step S1, the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere, and the definitions of the oxygen atmosphere and the air atmosphere are conventional in the art.

[0052] According to an embodiment of the present disclosure, in step S2, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere, and the definitions of the nitrogen atmosphere and the argon atmosphere are conventional in the art.

[0053] According to one embodiment of the present disclosure, in step S1, the first heat treatment is performed by roasting, which can be performed in a sagger; the conditions of the first heat treatment include: a time of 10-20 hours and a temperature of 600-850°C; preferably, the time is 12-18 hours and a temperature of 700-800°C; the ternary material formed at this temperature has good capacity and stability.

[0054] According to one embodiment of the present disclosure, in step S2, the second heat treatment is performed by roasting, which can be performed in a sagger; the conditions of the second heat treatment include: a time of 1-5 hours and a temperature of 400-700°C; preferably, the time is 1.5-4 hours and a temperature of 500-600°C; at this temperature, the selenium source can be fully decomposed / gasified, thereby reacting with the ternary material and forming a relatively uniform coating layer.

[0055] According to an embodiment of the present disclosure, step S2 is performed in a tube furnace, including: placing a selenium source upstream of the tube furnace, and placing a first solid material downstream of the tube furnace; wherein the selenium source generates a fluid containing selenium under high temperature, and the fluid containing selenium flows to the downstream of the tube furnace and contacts the first solid material. The fluid containing selenium reacts with the surface metal element in the first solid material to form a metal selenide (M-Se), thereby forming a structure in which the metal selenide is coated on the surface of the particles.

[0056] The third aspect of the present disclosure provides a surface selenium-doped high-nickel ternary material prepared by the method described in the second aspect of the present disclosure. The above material has the same characteristics as the surface selenium-doped high-nickel ternary material described in the first aspect of the present disclosure, and will not be described in detail here.

[0057] A fourth aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the surface selenium-doped high-nickel ternary material as described in the first aspect or the third aspect of the present disclosure.

[0058] According to one embodiment of the present disclosure, the negative electrode is conventional in the art, and for example may include one or more of a lithium sheet, a carbon material, and a silicon-carbon composite material.

[0059] According to one embodiment of the present disclosure, the electrolyte is conventional in the art, for example, may include one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, lithium hexafluorophosphate and dimethyl carbonate.

[0060] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.

[0061] The raw materials used in the examples were all purchased from commercial sources and were of analytical grade unless otherwise specified.

[0062] The average particle size was measured using a MasterSizer 2000 laser particle size analyzer produced by Malvern, UK.

[0063] The instrument model of the scanning electron microscope was FEIQUANTA400, and the method was an accelerating voltage of 20 kV;

[0064] The X-ray photoelectron spectroscopy test instrument model is the American Thermo Fisher Thermo ESCALAB 250, and the method is to use an Al Kα X-ray emission light source.

[0065] Test method for material chemical formula: Inductively coupled plasma mass spectrometry.

[0066] Example 1

[0067] The surface selenium-doped high-nickel ternary material A1 was prepared by the following steps:

[0068] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.03:1 for 3 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 750°C for 15 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0069] Among them, the average particle size of the high-nickel ternary precursor is 6.8 μm;

[0070] (2) Under a nitrogen atmosphere, the selenium powder and the first solid material were placed in the upstream and downstream of the tube furnace in a molar ratio of 0.1:10, and a second heat treatment was performed at a temperature of 550°C for 2 hours. After cooling to room temperature, a surface selenium-doped high-nickel ternary material A1 was obtained with an average particle size of 8.0 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O 1.992 Se 0.008 ;

[0071] X-ray photoelectron spectroscopy was performed on the high-nickel ternary material A1. According to the results, there is a peak at 53-56eV in the XPS spectrum of the Se 3d orbital, which indicates that in the particles, the selenium element exists in the form of metal selenides. The metal selenides exist on the surface of the particles. The metal selenides include Ni selenides, Co selenides and Mn selenides.

[0072] Example 2

[0073] The surface selenium-doped high-nickel ternary material A2 was prepared by the following steps:

[0074] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.05:1 for 2 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 760°C for 15 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0075] Among them, the average particle size of the high-nickel ternary precursor is 6.8 μm;

[0076] (2) Under a helium atmosphere, the selenium powder and the first solid material were placed in the upstream and downstream of a tube furnace in a molar ratio of 0.5:10, and a second heat treatment was performed at a temperature of 500°C for 3 hours. After cooling to room temperature, a surface selenium-doped high-nickel ternary material A2 was obtained, with an average particle size of 9.0 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O 1.967 Se 0.033 ;

[0077] X-ray photoelectron spectroscopy was performed on the high-nickel ternary material A2. According to the results, there is a peak at 53-56eV in the XPS spectrum of the Se 3d orbital, which indicates that in the particles, the selenium element exists in the form of metal selenides. The metal selenides exist on the surface of the particles. The metal selenides include Ni selenides, Co selenides and Mn selenides.

[0078] Example 3

[0079] The surface selenium-doped high-nickel ternary material A3 was prepared by the following steps:

[0080] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.05:1 for 2 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 760°C for 18 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0081] Among them, the average particle size of the high nickel ternary precursor is 10.0 μm;

[0082] (2) Under a nitrogen atmosphere, the selenium powder and the first solid material were placed in the upstream and downstream of the tube furnace in a molar ratio of 1:10, and a second heat treatment was performed at a temperature of 550°C for 2 hours. After cooling to room temperature, a surface selenium-doped high-nickel ternary material A3 was obtained with an average particle size of 11.0 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O 1.929 Se 0.071 ;

[0083] X-ray photoelectron spectroscopy was performed on the high nickel ternary material A3, and the results are as follows Figure 2As shown, according to the results, there is a peak at 53-56 eV in the XPS spectrum of Se3d orbital, corresponding to the Se-M bond (M represents metal); this indicates that in the particles, selenium element exists in the form of metal selenide, and the metal selenide exists on the surface of the particles. The metal selenides include Ni selenide, Co selenide and Mn selenide.

[0084] Example 4

[0085] The surface selenium-doped high-nickel ternary material A4 was prepared by the following steps:

[0086] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.06:1 for 3 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 760°C for 18 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0087] Among them, the average particle size of the high-nickel ternary precursor is 14.0 μm;

[0088] (2) Under a nitrogen atmosphere, the selenium powder and the first solid material were placed in the upstream and downstream of the tube furnace in a molar ratio of 2:10, and a second heat treatment was performed at a temperature of 600°C for 2 hours. After cooling to room temperature, a surface selenium-doped high-nickel ternary material A4 was obtained, with an average particle size of 13.4 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O 1.857 Se 0.143 ;

[0089] X-ray photoelectron spectroscopy was performed on the high-nickel ternary material A4. According to the results, there is a peak at 53-56eV in the XPS spectrum of the Se 3d orbital; in the particles, the selenium element exists in the form of metal selenides, and the metal selenides exist on the surface of the particles. The metal selenides include Ni selenides, Co selenides and Mn selenides.

[0090] Example 5

[0091] The method of Example 1 was used to prepare the surface selenium-doped high-nickel ternary material A5, except that the LiOH·H2O in step (1) was replaced by Li2CO3 containing an equimolar amount of lithium element, and the high-nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 replaced by Ni 0.6 Co0.2 Mn 0.2 (OH)2; replacing the selenium powder in step (2) with ammonium selenite containing an equimolar amount of selenium;

[0092] The average particle size of the surface selenium-doped high-nickel ternary material A5 is 7.9 μm, and the chemical formula is LiNi 0.6 Co 0.2 Mn 0.2 O 1.994 Se 0.006 ;

[0093] X-ray photoelectron spectroscopy was performed on the high-nickel ternary material A5. According to the results, there is a peak at 53-56eV in the XPS spectrum of the Se 3d orbital, which indicates that in the particles, the selenium element exists in the form of metal selenides. The metal selenides exist on the surface of the particles. The metal selenides include Ni selenides, Co selenides and Mn selenides.

[0094] Example 6

[0095] The method of Example 1 is used to prepare the surface selenium-doped high-nickel ternary material A6, except that in step (2), the molar ratio of selenium powder to the first solid material is 5:10;

[0096] The average particle size of the surface selenium-doped high-nickel ternary material A6 is 9.8 μm, and the chemical formula is LiNi 0.8 Co 0.1 Mn 0.1 O 1.732 Se 0.268 ;

[0097] X-ray photoelectron spectroscopy was performed on the high-nickel ternary material A6. According to the results, there is a peak at 53-56eV in the XPS spectrum of the Se 3d orbital, which indicates that in the particles, the selenium element exists in the form of metal selenides. The metal selenides exist on the surface of the particles. The metal selenides include Ni selenides, Co selenides and Mn selenides.

[0098] Comparative Example 1

[0099] The high nickel ternary material D1 is prepared by the following steps:

[0100] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.03:1 for 3 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 750°C for 15 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0101] Among them, the average particle size of the high-nickel ternary precursor is 6.8 μm;

[0102] (2) Under nitrogen atmosphere, the first solid material was placed in a tube furnace for a second heat treatment at a temperature of 550° C. for 2 h. After cooling to room temperature, a high-nickel ternary material D1 was obtained with an average particle size of 8.0 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0103] Comparative Example 2

[0104] The high nickel ternary material D2 is prepared by the following steps:

[0105] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.05:1 for 2 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 760°C for 15 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0106] Among them, the average particle size of the high-nickel ternary precursor is 6.8 μm;

[0107] (2) In a helium atmosphere, the first solid material was placed in a tube furnace for a second heat treatment at a temperature of 500° C. for 3 h. After cooling to room temperature, a high-nickel ternary material D2 was obtained with an average particle size of 9.0 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0108] Comparative Example 3

[0109] The high nickel ternary material D3 is prepared by the following steps:

[0110] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.05:1 for 2 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 760°C for 18 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0111] Among them, the average particle size of the high nickel ternary precursor is 10.0 μm;

[0112] (2) Under nitrogen atmosphere, the first solid material was placed in a tube furnace for a second heat treatment at a temperature of 550° C. for 2 h. After cooling to room temperature, a high-nickel ternary material D3 was obtained with an average particle size of 11.0 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0113] Comparative Example 4

[0114] The high nickel ternary material D4 is prepared by the following steps:

[0115] (1) LiOH·H2O and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 was mixed evenly in a planetary ball mill at a molar ratio of 1.06:1 for 3 hours, the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere at a temperature of 760°C for 18 hours, and the obtained solid product was crushed and sieved to obtain a first solid material;

[0116] Among them, the average particle size of the high-nickel ternary precursor is 14.0 μm;

[0117] (2) Under nitrogen atmosphere, the first solid material was placed in a tube furnace for a second heat treatment at a temperature of 600°C for 2 hours. After cooling to room temperature, a high nickel ternary material D4 was obtained with an average particle size of 13.4 μm and a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0118] Figure 3 X-ray photoelectron spectra of Co 2p orbitals in high nickel ternary materials A3 and D3 prepared in Example 3 and Comparative Example 3; Figure 3 It can be seen that compared with the peak position of the Co 2p orbital in D3, the peak position of the Co 2p orbital in A3 shifts toward the low energy direction, indicating that at least part of the O element is replaced by the Se element and bonds with the Co element, that is, forming Co selenide.

[0119] Figure 4 X-ray photoelectron spectra of Mn 2p orbitals in high nickel ternary materials A3 and D3 prepared in Example 3 and Comparative Example 3; Figure 4 It can be seen that compared with the peak position of the Mn 2p orbital in D3, the peak position of the Mn 2p orbital in A3 shifts toward the low energy direction, indicating that at least part of the O element is replaced by the Se element and bonds with the Mn element, that is, forming Mn selenide.

[0120] Figure 5 This is a scanning electron microscope image of the high nickel ternary material A4 prepared in Example 4; Figure 6 This is a scanning electron microscope image of D4 in the high nickel ternary material prepared in Comparative Example 4. Figure 5 and 6 It can be seen that A4 has a spherical morphology and size similar to D4, and the boundaries of the primary particles are obvious, indicating that the high-nickel ternary material with selenium doped on the surface can maintain its original morphology and size.

[0121] The electrochemical stability test of the high nickel ternary material prepared in Example A1 and Comparative Example D1 was carried out, and the specific steps are as follows:

[0122] The positive electrode material, conductive agent (acetylene black), and binder (polyvinylidene fluoride) were weighed in a mass ratio of 8:1:1 and mixed evenly with the solvent (N-methylpyrrolidone), coated on aluminum foil and cut into sheets as the positive electrode; then mixed with lithium sheet, electrolyte (1 mol·L -1 LiPF6 (ethylene carbonate / ethyl methyl carbonate / dimethyl carbonate solution, mass ratio of 1:1:1) and a separator (Celgard2300) were used to form a lithium-ion half-cell for electrochemical performance testing.

[0123] Performance test conditions: charge and discharge voltage range is 2.75-4.3V; charge and discharge rate is 0.1C for the first 4 times and 0.5C for the 5th time and thereafter.

[0124] Figure 1 Electrochemical cycle curves of high nickel ternary materials A1 and D1 prepared in Example 1 and Comparative Example 1.

[0125] according to Figure 1 It can be seen that when material A1 is used as the positive electrode material, the capacity retention rate after 200 cycles is 82.0%, and when material D1 not doped with selenium is used as the positive electrode material, the capacity retention rate after 200 cycles is 65.3%.

[0126] In summary, in the surface selenium-doped high-nickel ternary material disclosed in the present invention, the selenium element replaces at least part of the oxygen element, and at least part of the selenium element exists in the form of metal selenide, which can not only stabilize the metal elements on the surface of the material to improve the stability of the material itself, but also slow down the side reactions at the material-electrolyte interface. Using it as a positive electrode material for lithium-ion batteries can effectively improve the electrochemical cycle stability.

[0127] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0128] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0129] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A surface selenium-doped high-nickel ternary material, characterized in that: The surface selenium-doped high-nickel ternary material comprises a chemical formula of LiNi x Co y Mn z O 2-p Se p Particles, x+y+z=1, 0.6≤x≤0.9, 0.05≤y≤0.2, 0.05≤z≤0.2, 0<p≤0.2; In the XPS spectrum of the Se 3d orbital of the high-nickel ternary material, there is a peak at 53-56 eV.

2. The surface selenium-doped high-nickel ternary material according to claim 1, wherein: In the particles, at least part of the selenium element exists in the form of metal selenide; The metal selenide includes Ni selenide, Co selenide and Mn selenide; Optionally, the metal selenide is present on the surface of the particles.

3. The surface selenium-doped high-nickel ternary material according to claim 1, wherein: The average particle size of the particles is 3-18 μm.

4. A method for preparing a surface selenium-doped high-nickel ternary material, characterized in that: The method comprises the following steps: S1, mixing a lithium source and a high-nickel ternary precursor in a solid phase, and subjecting the obtained mixed material to a first heat treatment in an oxygen-containing atmosphere to obtain a first solid material; S2. Contacting the selenium source with the first solid material, and performing a second heat treatment under an inert atmosphere.

5. The method according to claim 4, wherein: The chemical formula of the high nickel ternary precursor is Ni a Co b Mn c (OH)2, a+b+c=1, 0.6≤a≤0.9, 0.05≤b≤0.2, 0.05≤c≤0.2; The average particle size of the high-nickel ternary precursor is 3-18 μm.

6. The method according to claim 4, wherein: The selenium source includes one or more of selenium, sodium selenite and ammonium selenite; The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

7. The method according to claim 4, wherein: In step S2, the molar ratio of the selenium source to the first solid material is (0.05-5):10, calculated as selenium element.

8. The method according to claim 4, wherein: In step S1, the first heat treatment is performed by calcination, and the conditions of the first heat treatment include: a time of 10-20 hours, a temperature of 600-850° C., and the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere; In step S2, the second heat treatment is performed by calcination, and the conditions of the second heat treatment include: a time of 1-5 hours, a temperature of 400-700° C., and the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

9. The method according to claim 4, wherein: In step S1, the solid phase mixing method includes solid phase ball milling for 1-5 hours.

10. The method according to claim 4, wherein: Step S2 is performed in a tube furnace, comprising: placing the selenium source upstream of the tube furnace, and placing the first solid material downstream of the tube furnace; The selenium source generates a fluid containing selenium under high temperature, and the fluid containing selenium flows to the downstream of the tube furnace and contacts the first solid material.

11. A surface selenium-doped high-nickel ternary material prepared by the method according to any one of claims 4 to 10.

12. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the surface selenium-doped high-nickel ternary material as described in any one of claims 1-3 and 11.